Urinary Tract Infections among HIV-Positive Pregnant Women in Mwanza City, Tanzania, Are High and Predicted by Low CD4+ Count - Tito Chaula; Jeremiah Seni; Nhandi Ng’walida; Alphaxaid Kajura; Mariam M. Mirambo; Rebekah DeVinney; Stephen E. Mshana (International Journal of Microbiology)
Introduction. Urinary tract infection (UTI) among pregnant women can lead to adverse maternal and foetal outcomes. UTI has been widely studied in the general obstetric population in Tanzania; the present study evaluated the magnitude, antimicrobial resistance, and predictors of UTI among HIV-positive pregnant women. Methods. Between March and May 2016 midstream urine samples from 234 women attending prevention of mother to child transmission of HIV (PMTCT) clinics were analyzed using standard methods. Data was analyzed by STATA version 11.0. Results. The prevalence of UTI was 21.4%, 50/234 [95% CI: 16.1–26.6]. The asymptomatically significant bacteriuria was higher than symptomatically significant bacteriuria (16.6% versus 4.7%, p<0.001). On multivariable logistic regression analysis, single marital status (OR: 2.6, 95% CI: 1.1–6.1, and p=0.026), low CD4+ counts of <200/μL (OR: 2.9, 95% CI: 1.1–7.7, and p=0.031), and having UTI symptoms (OR: 2.5, 95% CI: 1.1–6.0, and p=0.03) were independent predictors of UTI. Escherichia coli predominated (57.7%) and exhibited a low prevalence of resistance to nitrofurantoin (16.7%), gentamicin (10.0%), and ceftriaxone (13.3%). Four (13.3%) of these were extended-spectrum beta-lactamase producers. Conclusions. A considerable proportion of HIV-positive pregnant women in Mwanza have significant bacteriuria which calls for the need to introduce routine UTI screening at PMTCT clinics to guide specific treatment and prevent associated complications.